Comparison of Exposed Aggregate Cement Concrete Surface and Stone Mastic Asphalt Surface Noise Emissions by Close-Proximity Method - Blanka Hablovicova (MDPI AG, 2021)
In this study, results from long-term monitoring of the tyre/road noises of the exposed aggregate cement concrete (EACC) with the highest grain size of 8 mm and stone mastic asphalt (SMA) surface with the highest grain size of 11 mm performed by close-proximity (CPX) method are presented. There are certain concerns that the EACC surface will have inferior noise properties than SMA. These concerns are based on previous experience with the cement concrete surface with transverse tining texture which is very noisy. The main aim of this article is to demonstrate that these concerns are unfounded. A section of the motorway was chosen for the measuring and the testing speed for all measurements was 80 km·h−1. Provisional results (based on six years of monitoring) show that the noise levels measured on both these surface types are similar over their lifetime and exhibit logarithmic acoustic behaviour.